The Effect of Socialisation on Housewives' Knowledge in Understanding Social Entrepreneurship: Case Study in Kadudampit Village, Sukabumi - Yusuf Iskandar; Dede Suleman; Ujang Badru Jaman; Fachrizal Satrio Putro Yuwono; Tarisa Aulia Ananda (Westscience Press, 2024)
Social entrepreneurship is one of the effective ways to overcome social problems and empower the local economy, especially among housewives. This community service aims to socialise and improve the knowledge of housewives in Kadudampit Village, Sukabumi, regarding social entrepreneurship and evaluate their interest in engaging in social enterprises. This community service activity was conducted through several stages, including counselling, group discussions, and simulations. The results showed a significant improvement in participants' understanding of social entrepreneurship, with 85% showing a better experience and 60% expressing interest in starting a social enterprise. Despite barriers such as limited capital and technical knowledge, participants felt encouraged to contribute to social-based economic development in their villages. Follow-up recommendations include mentoring programmes and facilitating access to financing to ensure the sustainability of the planned social enterprises.